ANALISIS PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN PADA PEMERINTAHAN KOTA PARIAMAN - NOVIA CITRA DEWI; SELIA MARISKA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2018)
This study aims to obtain an overview of the implementation of financial SIMDA at the Head Office of Pariaman Tengah, East Pariaman Sub-District Office, Office of South Pariaman Subdistrict and Office of North Pariaman Sub-District. And know the understanding of employees in implementing SIMDA Finance and obstacles encountered in its application. Respondents in the study were four persons consisting of accounting and reporting staff. Data were collected through direct interview with respondents. The results of interviews and data that have been collected are analyzed by descriptive method using phenomenology approach. The results of the study indicate that in general employees have understood the meaning of financial SIMDA as well as description of its implementation related to input and output data. Constraints faced in the implementation of this SIMDA Finance applications SIMDA is rapidly expired, frequent offline network, there is no documentation about the flow chart summary that shows cash flow data, weak data management system, procedures to see the data incidental still too long, space is still inadequate offices as well as the occurrence of human error.